The art and soul of Dune Part Two - Lapointe, Tanya (Insight Editions, 2024)
The Art and Soul of Dune: Part Two captures the breathtaking behind-the-scenes journey behind the making of Dune: Part Two, the second film in director Denis Villeneuve's six-time Oscar-winning film adaptation of author Frank Herbert's science fiction classic. Written by Dune: Part Two producer Tanya Lapointe (p.g.a.), this visually dazzling exploration of the filmmaking process gives unparalleled insight into the project's genesis--from its striking environmental designs to its intricate costume concepts and landmark digital effects. The Art and Soul of Dune: Part Two also features exclusive interviews with key members of the cast and crew, including Denis Villeneuve, production designer Patrice Vermette, and many more, delivering a uniquely candid account of the hugely ambitious international shoot
"Dune : Part One and Part Two are based on the novel by Frank Herbert."--Cover
Keywords: Herbert, Frank -- 1920-1986 -- Dune; Villeneuve, Denis -- 1967-; Science fiction films / History and criticism; Herbert, Frank / Dune; Herbert, Frank / Settings; Dune (Imaginary place); Dune, part II (Motion picture); Films de science-fiction / Histoire et critique; Dune (Lieu imaginaire); Illustrated works; Ouvrages illustrés; Bildband